KOMPLIKASI VENTRIKULOPERITONEAL SHUNT PADA PASIEN PEDIATRIK USIA 0-2 TAHUN DI RUMAH SAKIT UMUM PUSAT NASIONAL DR CIPTOMANGUNKUSUMO - Samsul Ashari; Bhayu Rizallinoor; Hilman Mahyudin; Moh. Saekhu; Renindra Ananda Aman; David Tandian; Abdi Reza; Setyo Widi Nugroho (NEURONA, 2021)
Introduction: Ventriculoperitoneal shunt is the procedure of choice in the management of hydrocephalus. However,the ventriculoperitoneal shunt procedure also carries a risk of complications. In Indonesia, data on the incidence andprevalence of ventriculoperitoneal shunt complications have not been obtained.Aim: In this study, we examined the complications of shunts and the factors associated with the duration of timeMethods: This study is a retrospective study of pediatric patients aged 0-2 years with hydrocephalus who underwentventriculoperitoneal shunt surgery for the first time at Cipto Mangunkusumo Hospital in 2015-2020 and e????periencedcomplications. The duration of time the complications occurred was divided into before and after six months. Demographicdata, clinical data, and types of complications were analyzed descriptively.Result: From ????anuary 2015 to March 2020 at Cipto Mangunkusumo Hospital, 168 ventriculoperitoneal shuntoperations were performed at 0-2 years. It was found that 20 patients (12%) e????perienced complications with a duration offewer than si???? months by ????.8% and more than si???? months by 4.2%. The total complications that occurred were mechanicalcomplications (????.2%), infection (3.6%), and over drainage (1.2%).Discussion: The percentage of complications of ventriculoperitoneal shunt in patients aged 0-2 years at CiptoMangunkusumo Hospital, in the first si???? months was ????.8%, with the highest incidence was infection (3.6%) which waslower than the literature, while the percentage of complications of ventriculoperitoneal shunts which more than six monthswere 4.2% and caused mainly by distal malfunction (3%).Keywords: aged 0-2 years, complications, pediatric, ventriculoperitoneal shunt